Management of confirmed mushroom poisoning - Kinga Brzuszkiewicz; Kinga Pożarowska; Gracjan Rudziński; Borys Łozowski; Natalia Kusak; Arkadiusz Grunwald; Michał Tchórz (Kazimierz Wielki University, 2022)
During the autumn season, it is common for mushroom pickers to eat poisonous mushrooms. This is due to many reasons, including the ignorance of pickers. The most common is the misidentification of inedible species as edible mushrooms. The result is poisoning, which in many cases requires hospitalization. This paper presents a case report of toadstool poisoning by a 62-year-old female patient. In addition, other relevant publications on intoxication, diagnostic methods and treatment are reviewed. The purpose of this paper is to present the management and treatment of a case of toadstool poisoning. The effects of mushroom poisoning can range from mild disorders, mainly gastrointestinal to organ failure and even death. Significant elevations of liver enzymes and prothrombin time are important in laboratory tests in cases of intoxication. Treatment most often involves specific antidotes, such as Sylimarin, Acetylcysteine. The diagnosis in most cases is made on the basis of the clinical picture and a thorough interview with the patient, and the diagnosis is established by detecting toxins in a urine test. The prognosis is better if patients with toadstool poisoning are admitted to the hospital early. It is worth noting that gastrointestinal syndromes can also result from eating raw or inadequately cooked mushrooms, and by eating them excessively or too often. Proper diagnosis and treatment of mushroom poisoning can save lives. It is very important to raise public awareness of mushroom poisoning, as well as early detection of potential signs of intoxication. Cooperation with the poison center and mycologists is very important, especially in high-risk cases.